Estimation oxidant and anti oxidant of patients with changeful heart discomfort and myocardiac breach of Diwaniya-Iraq - mahdi kareem , Hussein (Al-Qadisiyah Journal of Pure Science, 2019)
The present study aimed check the relation between level oxidants and Anti- oxidants of person at changeful heart discomfort (type of heart disease) , myocardiac breach while identify role oxidants in develop disease of individual province of Diwaniya-Iraq. the study of patients who are divided into two group patient (A) included 45 patients changeful heart discomfort pectoris in different age , patient (B) included 45 patients with acute myocardiac breach at different age and group (C) 45 as control health .The results demonstrate show a significant decrease (p≤ 0.05 ) in vitamin E, C, glutathion peroxidas and Glutathione (GSH) in group A,B and significant increase (p≤ 0.05) in caeruloplasmin , ferroxidase enzyme, and Malondialdehyde (MDA) of individual changeful heart attack and myocardiac breach .The conclusion of study the negative role of high free radical was subsisted heart disorder progress. heart attack reduces oxygen access to the heart muscle. Oxygen depletion leads to increased free radicals that contribute to heart problems.